Cu/Pd‐Catalyzed One‐Pot Synthesis of 2‐(1, 2, 3‐Triazolyl)methyl‐3‐alkynylImidazo[1, 2‐a]pyridines Involving Sequential SN Reaction/[3+2] Cycloaddition/Sonogashira Coupling Reactions. Issue 35 (15th September 2021) - Qami, Abdelkarim El; Jismy, Badr; El Hakmaoui, Ahmed; Akssira, Mohamed; Abarbri, Mohamed
Abstract: An efficient one‐pot regioselective synthesis of 2‐(1, 2, 3‐triazolyl)methyl‐3‐alkynyl imidazo[1, 2‐ a ]pyridines is reported under simple and mild reaction conditions. The new imidazo[1, 2‐ a ]pyridines embedded with 4‐substituted‐[1, 2, 3]‐triazole were obtained in good to excellent yields from 2‐(chloromethyl)‐3‐iodo imidazo[1, 2‐ a ]pyridines via a one‐pot sequence involving an SN reaction with azide, followed by copper‐catalyzed [3+2]cycloaddition and a Sonogashira coupling reaction. Abstract : An efficient and a simple method for the one‐step synthesis of 2‐(1, 2, 3‐triazolyl)methyl‐3‐alkynyl imidazo[1, 2‐ a ]pyridines has been developed. The new imidazo[1, 2‐ a ]pyridines embedded with 4‐substituted‐[1, 2, 3]‐triazole were obtained in good to excellent yields from 2‐(chloromethyl)‐3‐iodo imidazo[1, 2‐ a ]pyridines via a sequence involving azidation/[3+2]cycloaddition followed by a Sonogashira coupling reaction.